Walter-Kempowski-Handbuch - Damiano, Carla Ann; Grünes, Andreas; Feuchert, Sascha; Weber, Christiane (De Gruyter Reference, 2020)
Until now, literary researchers on Walter Kempowski (1929–2007) have lacked a comprehensive reference work that considered both the life and work of Germany’s most important author of the post-war period. The Kempowski Handbook fills this gap – in the book, leading scholars elucidate Kempowski’s biography, artistic oeuvre, and the current state of research.